Global Citizenship Education in Curriculum Development: Perspectives from Asian Universities - Patrick A. V. Roussel; Georges Kevin Ndongmo; Nathalie Picard (International Journal of Studies in International Education, 2024)
This paper explores the integration of global citizenship education (GCE) in the curricula of select Asian universities. Through a survey of faculty members and curriculum developers, the study analyzes current GCE initiatives and identifies key factors that influence their implementation. Findings suggest that while GCE is increasingly valued, there are challenges related to funding, curriculum rigidity, and cultural relevance. The study proposes strategies for effectively embedding GCE in higher education curricula to cultivate global competencies in students.